Hands-On Generative Adversarial Networks with PyTorch 1.x : Implement next-generation neural networks to build powerful GAN models using Python /: Implement next-generation neural networks to build powerful GAN models using Python. (2019) - Hany, John; Walters, Greg
No abstract available